Remarques sur le parler roman et les noms de lieu du nord-ouest de la Loire-Atlantique - Hervé Tremblay-Couedel (La Bretagne Linguistique, 1989)
My toponymic study has examined a part of the north-western part of the Loire-Atlantique, in which I retained 27 communes (or 34 parishes). This area is naturally limited by the Don valley to the north, the Brière to the west and the Loire to the south. But the heart of it is the Haut-Brivet and Isac basins. My aim was to see how the distribution of names in -ac in this area could be explained. In addition to written sources, I added ancient forms and, above all, dialectal pronunciation. These two indispensable requirements have been invaluable aids to the study of toponyms in a region where Breton has long since been replaced by a Romance dialect.